ANALISIS PERKEMBANGAN KEMAMPUAN KEUANGAN DAERAH DALAM MENDUKUNG PELAKSANAAN OTONOMI DAERAH DI KABUPATEN TRENGGALEK TAHUN 2013-2015 - Nimas Agustin Candra Sujarwo; Abdul Wahid Mahsuni; M. Cholid Mawardi (Universitas Islam Malang, 2017)
This research is conducted in Trenggalek Regency because of the potential of natural resources in Trenggalek which is so big especially in terms of tourism and agrarian sector. With the existence of regional autonomy should this sector can be developed optimally as one of source of original revenue area. Trenggalek is very interesting to investigate after the new policy about the government that is regional autonomy which gives opportunity to local government to more optimize the potential of natural resources that exist. In addition, the lack of research on the evaluation of existing development in this regency after the regional autonomy is one of the lack of reference in the development of this regency, so it is expected that this research can be considered by the local government of Trenggalek Regency in developing the economy and also determine the development targets to increase people welfare. Given the economic problems in the Trenggalek area with a lot of local revenue sources we can see whether the Trenggalek Regency government has been able to optimize every available source of income to accelerate or support the implementation of regional autonomy. By using sample of financial report of Regency of Trenggalek year 2013-2015, with result of research as a whole result of calculation of Independence Ratio, Effectiveness, Efficiency, and Activity got result that Trenggalek Regency not support implementation of Regional Autonomy.